Mapping the central neurocircuitry that integrates the cardiovascular response to exercise in humans - Basnayake, S; Green, A; Paterson, D (2012)
There are abundant animal data attempting to identify the neural circuitry involved in cardiovascular control. Translating this research into humans has been made possible using functional neurosurgery during which deep brain stimulating electrodes are implanted into various brain nuclei for the treatment of chronic pain and movement disorders. This not only allows stimulation of the human brain, but also presents the opportunity to record neural activity from various brain regions. This symposium review highlights key experiments from the past decade that have endeavoured to identify the neurocircuitry responsible for integrating the cardiovascular response to exercise in humans. Two areas of particular interest are highlighted: the periaqueductal grey and the subthalamic nucleus. Our studies have shown that the periaqueductal grey (particularly the dorsal column) is a key part of the neurocircuitry involved in mediating autonomic changes adapted to ongoing behaviours. Emerging evidence also suggests that the subthalamic nucleus is not only involved in the control of movement, but also in the mediation of cardiovascular responses. Although these sites are unlikely to be the 'command' areas themselves, we have demonstrated that the two nuclei have the properties of being key integrating sites between the feedback signals from exercising muscle and the feedforward signals from higher cortical centres. © 2011 The Authors. Experimental Physiology © 2012 The Physiological Society.